The development of English reading comprehension learning activities with SQ4R of grade 6 students - Phurabat, Suwichaya; Janghan, Surakarn; Nakhunsong, Tassanee (Journal for Developing the Social and Community, 2023)
The objectives of this research were: 1. To develop English reading comprehension activities of grade 6 students using SQ4R technique according to 80/80 criteria. The understanding of grade 6 students by using SQ4R technique between after school and 70% criteria 3. To study the students’ satisfaction with SQ4R learning activities of grade 6 students 33 Prathomsuksa 6 students in the second semester of the academic year 2021 using a random selection method. The research instruments were 6 SQ4R learning activity plans, a reading comprehension test and a student satisfaction questionnaire. The statistics used for data analysis were mean () Percentage (%) Standard Deviation (S.D.) and hypothesis testing using t - test (Dependent Samples) The results showed that 1) An English reading comprehension activity using SQ4R technique of Grade 6 students had an efficiency of the process of 79.63/80.25 2) Students studying using SQ4R techniques have a reading ability in English for comprehension, amounting to 70 percent. 3) Students are very satisfied with their learning activities with SQ4R overall to (=3.52, S.D.=0.72)